Phospholipases in physiology and pathology - Chakraborti, Sajal (Cambridge, Massachusetts Academic Press, 2023)
"Phospholipases in Physiology and Pathology presents a comprehensive overview on the physiology and pathology of phospholipases. This seven-volume set considers the biochemical and molecular mechanisms of normal and abnormal cell function upon dysregulation of phospholipases in different diseases. Volumes cover signal transduction mechanisms, implications in cancer, infectious diseases, neural diseases, cardiovascular diseases and other diseases, implications in inflammation, apoptosis, gene expression and non-coding RNAs, the role of natural and synthetic compounds, and stem cell therapies, nanotechnology-based therapies, and more. Together, these volumes give researchers critical insight on the mechanistic and therapeutic aspects of phospholipases."
Includes bibliographical references and index.
Keywords: Cellular signal transduction; Phospholipases; Enzymes -- Pathophysiology; Enzymes -- Physiological effect